The Study of Biomechanics and Clinical Anatomy on a Novel Plate Designed for Posterolateral Tibial Plateau Fractures via Anterolateral Approach - Ren, Weizhi; Zhang, Wen; Jiang, Shijie; Peng, Jian; She, Chang; Li, Liubing; Mao, Yongtao; Zhou, Haibin; Xu, Wei (Frontiers in Bioengineering and Biotechnology, 2022)
There is no consensus about the optimal internal fixation selection for treatment of pos-terolateral tibial plateau fracture. This study described a novel plate through an anterol-ateral approach for posterolateral tibial plateau fractures (PTPFs). We evaluated the biomechanical performance of a novel plate and two conventional internal implants and investigated the anatomic feasibility of the novel plate. The fracture models were randomly assigned into six groups: Groups A-C were the model groups of posterolateral split fracture, ﬁxed with the posterior buttress plate, the lateral locking plate, and the novel plate, respectively. Groups D-E were the model groups of posterolateral depression fracture, ﬁxed with the posterior buttress plate, the lateral locking plate, and the novel plate, respectively. We evaluated the biomechanical performance of six model groups by the biomechanical testing and finite element analysis. Progressively increasing axial compressive loads were applied to each synthetic fracture model by using a customized indentor under 250 to 750 N loads. Meanwhile, we dissected 12 fresh fro-zen knee specimens and fixed them with the novel plate through the anterolateral ap-proach. We recorded the adjacency of the novel plate to important anatomic structures. Biomechanical testing showed that the novel plate had the least displacement, followed by the posterior buttress plate, and the lateral plate had the most displacement in poster-olateral split fracture. There was no signiﬁcant difference in the displacement between the novel plate and the lateral plate at different loads in posterolateral depression frac-tures. And the posterior buttress plate showed the most displacement. In the finite ele-ment analysis, the maximum stress values of Groups A, B, and C were 383.76, 414.63, 305.07 MPa under the load of 750 N, respectively. The maximum stress values of Groups D, E, and F were 474.28, 436.31, and 413.4 MPa under the load of 750 N, re-spectively. In the anatomic study, the placement of the novel plate had a low risk of damage to the important anatomic structures of knee posterolateral corner. The novel plate could be a great choice for the treatment of PTPFs due to better biomechanical performance and easy manipulation.